Recent advances in chiral carbonized polymer dots: From synthesis and properties to applications. (October 2020) - Ru, Yi; Ai, Lin; Jia, Tongtong; Liu, Xingjiang; Lu, Siyu; Tang, Zhiyong; Yang, Bai
Graphical abstract: Highlights: Synthetic strategies for chiral carbonized polymer dots are introduced. The chiroptical origins of carbonized polymer dots are discussed. Chiral carbonized polymer dots possesses great advantages in chiral recognition, chiral catalysis, and biology. Challenges and opportunities in the future development of chiral carbonized polymer dots are considered. Abstract: The outstanding properties of carbon dots (CDs), including biocompatibility, low toxicity, photoluminescence, and easy synthesis and modification, make them strong competitors to traditional semiconductor quantum dots. Chirality exists widely in nature and plays important roles in life sciences and materials sciences. The application of chirality to CDs generates a new class of potentially valuable CDs materials, chiral CDs, that may be useful in areas such as enantiomeric recognition and separation, chiral catalysis, bioimaging, and biomedicine. In the strict sense, chiral CDs synthesized by a "bottom-up" method should be classified as carbonized polymer dots (CPDs), and we therefore propose that such chiral CDs be termed chiral CPDs (Ch-CPDs). Here, we provide the first comprehensive review of recent achievements in Ch-CPDs synthesis methodology, properties, and applications, and discuss the challenges to be overcome in their future development.